MACAPATAN SURAT YUSUF DALAM TRADISI TINGKEBAN DI DESA WILAYUT, KECAMATAN SUKODONO, KABUPATEN SIDOARJO KAJIAN SASTRA LISAN ALBERT B.LORD - , NAILA NILOFAR, Dr. Novi Siti Kussuji I, M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Macapatan Surat Yusup is an oral literature that still exist in Wilayut, Sukodono, Sidoarjo. This tradition is used by the villagers in the seven monthly of women pregnancy to pray for the health and safety of the pregnant mother and her unborn child. This Macapatan Surat Yusup research needs to be done because the tradition is one of the national cultural assets that need to be developed. This study used Albert B. Lord approach of oral literature. Orality aspects in the oral literary theory of Albert B. Lord include: composition, transmission, performance, formulas, themes, and function. Based on this formulation, the problem in this research are how performance, composition, and transmission of macapatan Surat Yusuf?